Isolation of uranium(iii) primary phosphido complexes. Issue 69 (11th August 2022) - Perales, Diana; Bhowmick, Rina; Zeller, Matthias; Miro, Pere; Vlaisavljevich, Bess; Bart, Suzanne C.
Abstract : Low-valent uranium(iii ) primary phosphido complexes supported by hydrotris(3, 5-dimethylpyrazolyl)borate (Tp*) were synthesized with phosphines of varying steric and electronic profiles. Abstract : Low-valent uranium(iii ) primary phosphido complexes supported by hydrotris(3, 5-dimethylpyrazolyl)borate (Tp*) were synthesized with phosphines of varying steric and electronic profiles. Compounds were characterized by multinuclear NMR spectroscopy ( 1 H, 11 B, 31 P NMR), infrared spectroscopy, electronic absorption spectroscopy, X-ray crystallography, and quantum chemical calculations.